2014
DOI: 10.1039/c4cc01815j
|View full text |Cite
|
Sign up to set email alerts
|

A unique copper-catalyzed cross-coupling reaction by hydrogen (H2) removal for the stereoselective synthesis of 3-phosphoindoles

Abstract: The first Cu(i)-catalyzed cross-coupling reaction by hydrogen (H2) removal for the stereoselective synthesis of 3-phosphoindoles is reported. Going beyond the oxidative dehydrogenative coupling reactions reported recently, this reaction completely omits the oxidant and base, producing hydrogen (H2) as the only byproduct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…N-Unsubstituted ethyl indole-2-carboxylate also reacts efficiently, the corresponding products being obtained in high yields (131b,f). 245 Steric effects have no appreciable influence: good yields of the products were observed for the substrates having a Me group in position 4, 5, 6 or 7 (phosphonates 131h ± k). Studying the electronic effects showed that electron-donating groups improve the reactivity of substrates compared to electron-withdrawing ones.…”
Section: Synthesis Of 3-phosphoindoles Via Crosscoupling Reactionmentioning
confidence: 99%
See 4 more Smart Citations
“…N-Unsubstituted ethyl indole-2-carboxylate also reacts efficiently, the corresponding products being obtained in high yields (131b,f). 245 Steric effects have no appreciable influence: good yields of the products were observed for the substrates having a Me group in position 4, 5, 6 or 7 (phosphonates 131h ± k). Studying the electronic effects showed that electron-donating groups improve the reactivity of substrates compared to electron-withdrawing ones.…”
Section: Synthesis Of 3-phosphoindoles Via Crosscoupling Reactionmentioning
confidence: 99%
“…3-Phosphoindoles represent novel second-generation non-nucleoside reverse transcriptase inhibitors (NNRTIs), demonstrating an excellent potency in vitro agaist wild-type and NNRTI-resistant type of HIV-1. 252 ± 256 In the primary study, 245 Yang and co-workers chose ethyl N-methylindole-2-carboxylate (133a) and phosphine oxide Ph 2 P(O)H (92) as model substrates. A broad screening for catalysts, solvents and temperatures was performed.…”
Section: Synthesis Of 3-phosphoindoles Via Crosscoupling Reactionmentioning
confidence: 99%
See 3 more Smart Citations